A Field Study Into Hong Kong’s Wet Markets: Raised Questions Into the Hygienic Maintenance of Meat Contact Surfaces and the Dissemination of Microorganisms Associated With Nosocomial Infections - Lo, Man Ying; Ngan, Wing Yui; Tsun, Shue Man; Hsing, Huey-Leng; Lau, Kin Tak; Hung, Hing Pui; Chan, Si Lok; Lai, Yan Yin; Yao, Yuan; Pu, Yang; Habimana, Olivier (Frontiers in Microbiology, 2019)
Millions every day purchase their raw meat in wet markets around the globe, especially in Hong Kong city, where modern and a traditional way of living is made possible. While food hygiene standards in Hong Kong have more recently focused on the safety of meat sold in these wet markets, the hygienic surface level of wooden cutting boards used for processing meats is seldom observed. This original study performed microbial community profiling, as well as isolating and identifying various strains multiple wooden cutting boards from nine wet markets located on Hong Kong Island. Our study also investigated the efficiency of scraping the surface of cutting boards as a traditional cleaning technique in Hong Kong. Results indicate that these hygienic practices are inefficient for guarantying proper surface hygiene as some most tested cutting boards were found to harbour microbial species typically associated with hospital nosocomial infections, such as Klebsiella pneumoniae. Further analysis also led to discovering the presence of antibiotic-resistant genes (ARGs) among isolated strains. Our results showcase the significance and effects of cross-contamination in Hong Kong wet markets, especially with regards to the potential spreading of clinically-relevant strains and ARGs on food processing surfaces. This study should, therefore, serve as a basis to review current hygienic practices in Hong Kong’s wet market on a larger scale, thereby improving food safety and ultimately, public health.